Three-dimensional, three-component wall-PIV - Berthe, André; Kondermann, Daniel; Christensen, Carolyn; Goubergrits, Leonid; Garbe, Christoph S.; Affeld, Klaus; Kertzscher, Ulrich R. (Experiments in fluids, 2010)
This paper describes a new time-resolved three-dimensional, three-component (3D-3C) measurement technique called wall-PIV. It was developed to assess near wall flow fields and shear rates near non-planar surfaces. The method is based on light absorption according to Beer-Lambert’s law. The fluid containing a molecular dye and seeded with buoyant particles is illuminated by a monochromatic, diffuse light. Due to the dye, the depth of view is limited to the near wall layer. The three-dimensional particle positions can be reconstructed by the intensities of the particle’s projection on an image sensor. The flow estimation is performed by a new algorithm, based on learned particle trajectories. Possible sources of measurement errors related to the wall-PIV technique are analyzed. The accuracy analysis was based on single particle experiments and a three-dimensional artificial data set simulating a rotating sphere.
Gesehen am 23.01.2023